II. Mahmut’un Temel Eğitimin Zorunluluğuna İlişkin 1824 Tarihli Talim-i Sıbyan Fermanının Çocuk Hakları Açısından İncelenmesi - Gurbetoğlu, Ali; Gurbetoğlu, Ali (My University, 2020)
Çocuk hakları ve çocuk işgücünün istismarı tarihin en köklü çocuk sorunlarındandır. Çocuk hakları,doğrudan çocukları korumaya dönük yasal bir metin halinde 20. yy. başlarında Batı dünyasında gündemegelmiştir. Bu konuda en kapsamlı yasal belge 1989 tarihli “Birleşmiş Milletler Çocuk Hakları Sözleşmesi”dir.Eski Türk kültüründe çocuğun korunması ve yetiştirilmesine ilişkin törelerle belirlenmiş birtakım uygulamalarmevcuttur. Osmanlı’da 1824 tarihli “Talim-i Sıbyan Fermanı”, bu alanda yaşanan problemlerin çözümüneyönelik ilk yasal yazılı belgelerden biridir. Bu ferman daha çok temel eğitimi zorunlu hale getiren ilk yasalmetin olarak görülmüştür. Türkiye'de eğitimi zorunlu kılan ilk belgelerden biri olarak fermana bilimselçalışmalarda sıklıkla atıfta bulunulmuştur. İçeriğinde, çocuk işgücünün istismar edilmesinin önlenmesi veçocukların eğitim yoluyla hayata hazırlanması konusuna vurgu yapılmıştır. Türkiye'de çocuk hakları alanındailk yazılı yasal belge olarak bilinen bu düzenleme içeriği itibariyle önem kazanmaktadır. Bu bağlamda ferman,çocuk hakları alanında hem dünyada hem de Türkiye'de en önemli belgelerden biri olmuştur. Bu çalışmanıntemel amacı II. Mahmut'un 1824 tarihli “Talim-i Sıbyan Fermanını” incelemek ve tanıtmak, bir diğer amacıise ilgili ferman’ı çocuk hakları açısından değerlendirmektir. Araştırma, nitel yönteme dayalı dokümanincelemesi deseninde yapılmıştır. Çalışmada “Talim-i Sıbyan Fermanı” temel kaynak olarak kullanılmıştır.Söz konusu ferman Ahmet Cevdet Paşa’nın “Tarih-i Cevdet” adlı eserinin Osmanlıca aslından elde edilmiştir.Fermanın içeriği Osmanlıca aslıyla verilmiş ayrıca günümüz Türkçesine de aktarılmıştır. Ferman’ın 1989tarihli Birleşmiş Milletler Çocuk Hakları Sözleşmesi’nde güvence altına alınan dört temel alandan “gelişme”ve “korunma” haklarını güvence altına almaya yönelik olduğu açıkça görülür. Fermanda öne çıkan iki husus;“temel eğitimin zorunluluğu” ve “çocuk işgücünün istismarının önlenmesi”dir. Bunlardan ilki, çocuğun“gelişim hakkı”, ikincisi, “korunma hakkı” ile ilgilidir. Ferman’da; temel dini bilgileri öğrenmenin önemivurgulanmış, aynı zamanda ebeveynlerin duyarsızlığı nedeniyle cehaletin yayılmasına işaret edilmiştir. Bununtemel sebebinin ailelerin çocukları para kazanmak amacıyla okul yerine çalışmaya göndermeleri olduğubelirtilmiştir. Bu nedenle, cehaletin toplumda yaygınlaşmasına ve çocukları gençken eğitmenin önemine dikkatçekilmiştir. Fermanda asıl amaç, ailelerin ve esnafın çocuk işgücünün sağlayacağı mali gelire karşı cesaretinikırmaktır. Çocukların istismarını önlemek amacıyla cezai müeyyideler öngörülmüştür. Bu çalışmada,eğitimciler tarafından iyi bilinen ve sıklıkla dile getirilen “Talim-i Sıbyan Fermanı” çağdaş çocuk haklarıaçısından değerlendirilmiştir. II. Mahmut, bu fermandaki hükümlerle çocukları ebeveynlerin ve esnafıninsafına terk etmemiş ve temel eğitimlerini zorunlu hale getirmiştir. Ferman ile çıraklık yerine, ergenlik çağınakadar çocukların temel eğitim okuluna gönderilmesi zorunlu hale getirildi. Böylece, ferman çocuğa eğitimhakkını kullanmada yardımcı olmuş, diğer yandan çocuk işgücünün kötüye kullanılmasını engellemiş veçocuğun fiziksel ve zihinsel gelişimi için daha sağlıklı bir ortam hazırlamıştır. Bu özelliğiyle Türk çocukluktarihinin yanı sıra Türk eğitim tarihi açısından da önemli bir belgedir. Ayrıca bu fermanın, dünya çocukluktarihinin ilk ve en önemli yasal belgelerinden biri olduğu söylenebilir. Bu ferman, 1989 tarihli BirleşmişMilletler Çocuk Hakları Sözleşmesi'nden yaklaşık bir buçuk yüzyıl önce çocukların “gelişme” ve “korunma”alanındaki haklarını gündeme getirmiştir. Bu bağlamda, ferman Türk ve dünya çocukluk tarihi açısından sonderece önemli bir belgedir.

The rights of the child and the exploitation of child labor are among the most fundamental child problems in history. The rights of the child have come into question in the Western world in the early 20th century as a legal text aimed directly at protecting children. The most comprehensive legal document on this subject is the “United Nations Convention on the Rights of the Child” of 1989. In ancient Turkish culture, there were some practices regarding the protection and upbringing of the child determined based on the customs. The “Edict of Talim-i Sıbyan (Education of Infants)” of 1824 in the Ottoman Empire is one of the first legal written documents aimed at solving the problems in this area. This edict was mainly deemed as the first legal text making primary education compulsory. As one of the first documents making primary education compulsory in Turkey, the edict has been referred to frequently in scientific studies. In the contents of the edict, the emphasis was placed on the prevention of exploitation of child labor and the preparation of children for life through education. This edict, which is known as the first written legal document in the field of the rights of the child in Turkey, gains importance with this content. In this context, the edict has been one of the most significant documents in the field of the rights of the child both in the world and in Turkey. The main objective of this study was to examine and introduce the “Edict of Talim-i Sıbyan (Education of Infants)” dated 1824 of Mahmut II. Another objective is to evaluate the relevant edict in terms of the rights of the child. The research was conducted in a document review pattern based on the qualitative method. The “Edict of Talim-i Sıbyan (Education of Infants)” was used as the main source in the study. The edict in question was extracted from the Ottoman original of Ahmet Cevdet Pasha's work named “Tarih-i Cevdet (History of Cevdet)”. The contents of the edict were given in Ottoman original as well as translated into modern Turkish. It is clear that the edict was intended to secure the rights of “development” and “protection” that are among the four basic areas secured in the 1989 United Nations Convention on the Rights of the Child. The two issues that come to the fore in the edict are the “necessity of primary education” and the “prevention of exploitation of child labor”. The first one relates to the child's “right to development” and the second one relates to the “right to protection”. The edict emphasized the importance of learning basic religious knowledge and also pointed to the spread of ignorance due to the indifference of parents. It is stated that the main reason for this is that the families send children to work instead of school to make money. For this reason, attention has been drawn to the spread of ignorance in society and the importance of educating children as they are young. The main purpose of the edict is to dissuade the families and tradesmen from the financial income provided by child labor. To prevent the abuse of children in that way, the edict prescribed penal sanctions. In this study, the “Edict of Talim-i Sıbyan (Education of Infants)”, which is well known and frequently referred to by educationists, was evaluated in terms of the contemporary rights of the child. With this edict, Mahmut II did not leave children at the mercy of the parents and tradesmen and made their primary education compulsory. Thanks to the edict, it was made compulsory for children to be sent to a primary education school, instead of apprenticeships, until adolescence period. Thus, the edict helped the child to exercise his/her right to education, on the one hand, prevented abuse of child labor and prepared a healthier environment for the child's physical and mental development, on the other hand. With this nature, the edict is an important document in terms of the history of Turkish education as well as the history of Turkish childhood. It can also be said that this edict is one of the first and most important documents in the world's childhood history. This edict brought the rights of children in the areas of “development” and “protection” into question nearly a century and a half before the 1989 United Nations Convention on the Rights of the Child. In this context, the edict is a very important document in terms of Turkish and world's childhood history.
Examination of Mahmut II's 1824 Edict of Talim-i Sıbyan (Education of Infants) on the Compulsion of the Primary Education in Terms of the Rights of the Child